2011
DOI: 10.1016/j.egypro.2011.05.084
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reverse current on the dark properties of photovoltaic solar modules

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
9
1
1
Order By: Relevance
“…When the I-V is plotted in a logarithmic scale, the resulting curve could be divided into three parts, and each part connotes a different quality of a module. This explanation is different from Sidawi et al's work where the authors presented only two parts of the curve [72]; here, the three parts are clearly seen. For the sake of easy comprehension, part two is first presented.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…When the I-V is plotted in a logarithmic scale, the resulting curve could be divided into three parts, and each part connotes a different quality of a module. This explanation is different from Sidawi et al's work where the authors presented only two parts of the curve [72]; here, the three parts are clearly seen. For the sake of easy comprehension, part two is first presented.…”
Section: Discussioncontrasting
confidence: 99%
“…This also relates to the recombination current within the module. The presence of a hot spot is believed to create weak regions in PV modules; this forces the electrons to flow in the reserve path of the p-i-n junction [40,72]. The third region of the semilog I-V curve extends from 15 V to 25 V, which is the range of a nominal operation voltage, and this region is associated with a high Figure 12, the combined semilog I-V is presented; the semilog of the short current I sc was extracted from the respective figures.…”
Section: Discussionmentioning
confidence: 99%
“…Several research papers studied the effect of reverse currents as a result of electrical stresses in solar cells and modules where I-V characteristics has shown to be strongly affected by these currents [7,8]. These studies however tackled the problem in the dark conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Field studies have shown that hot spotting is a major cause of panel performance degradation, even in systems employing bypass diodes [7]- [9]. Once a cell is degraded from hot spotting, it becomes a weak point in the string that causes performance reduction of the entire PV panel [10]. Hot spotting occurs more easily in a degraded cell, which exacerbates the hot spot degradation problem.…”
Section: Introductionmentioning
confidence: 99%